A bibliometric Analysis of Cancer Research in South Africa: study protocol - Moodley, Jennifer; Singh, Vedantha; Kagina, Benjamin M.; Abdullahi, Leila; Hussey, Gregory D. (BMJ open, 2015)
Cancer is an important and growing public health burden in South Africa (SA). Over the past few decades, there has been considerable scientific activity in cancer in SA. However, there has been limited analysis of cancer scientific publications. In this paper, we present a protocol for bibliometric analysis of cancer research conducted in SA. A comprehensive search of the journal databases PubMed, SCOPUS, Web of Science and EBSCO will be conducted to identify and retrieve data from primary peer-reviewed cancer research articles using a set of consensus search words. Articles that involve cancer research conducted in SA or using biological or clinical data from South African participants and published between 2004 and 2014 will be included in the study. Two independent researchers will screen the articles for eligibility. Bibliometric indicators and study characteristics will be extracted, entered into a database and analysed. The cancer disease site will be recorded and research will be classified using the Common Scientific Outline system. Data obtained will be analysed to determine SA's publication productivity index in cancer research. Annual trends in bibliometric indicators and the type of cancer research will be determined. The degree of collaboration in research conducted in SA will be analysed using co-authorship matrix software. A publication to disease type ratio will be used to assess scientific production relative to disease burden.
Keywords: cancer; bibliometric analysis